Story Retelling (SR) Technique in Improving Reading Comprehension of Sixth-Graders - Cupid Jones Risonar; Jayson Digamon; Jerome De La Pena; Ronnel Rey Delima (Philippine Association of Institutions for Research, Inc., 2021)
The PHIL-IRI results of the sixth graders during their fifth grade were seriously alarming. All learners were identified as frustration readers. Thus, this study aimed to improve sixth graders' reading comprehension through Story Retelling (SR) technique. The study used a pretest-post-test quasi-experimental design consisting of two intact classes with 43 grade 6 learners. One class was exposed to SR Technique, while the other was exposed to the traditional method. The comparison of posttest results revealed no significant difference in the comprehension level of the respondents with (p>.01) between groups. The data proved that SR did not significantly enhance the reading comprehension of the learners. There was a slight increase in the posttest mean scores of the experimental group. However, the increase was not significant. It showed that the learners lacked solid general knowledge and vast vocabulary, which are essential in reading. The interviews discovered that the learners were not exposed to the English language and were not adequately monitored about their academic progress. These pre-existing background conditions significantly affected the intervention, preventing a significant difference in the learners' reading comprehension. Based on the results, it is recommended that the Story Retelling (SR) technique is only introduced to the learners after they learn the basic reading skills, including vocabulary, and establish solid general knowledge. Moreover, the amount of time spent on the intervention added to the undesirable results. Thus, the intervention should be conducted in more than six weeks to achieve better results.